The Role of Blockchain in Enhancing Transparency in Global Supply Chains - Maria Santos; Jhose Ramoz (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Blockchain technology has emerged as a transformative solution for enhancing transparency and traceability in global supply chains. This paper explores the applications of blockchain in improving data accuracy and accountability, particularly in sectors such as agriculture, manufacturing, and pharmaceuticals. Through detailed case studies, the research demonstrates blockchain's effectiveness in reducing fraud, enhancing trust among stakeholders, and ensuring a more resilient supply chain framework. The findings suggest that implementing blockchain can significantly improve operational efficiencies and foster collaborative relationships across various industries.